Many Faces of Ad Hoc Transactions. - Tang, Chuzhe; Wang, Zhaoguo; Zhang, Xiaodong; Yu, Qianmian; Zang, Binyu; Guan, Haibing; Chen, Haibo (Communications of the ACM, 2025)
The article examines 91 ad hoc transactions as sourced from eight popular open source Web applications. The authors explain that sometimes developers may use locking primatives or manual validation to coordinate critical code fragments instead of relying on database transactions and they analyze these application-coordinated transactions as they improve performance in contentious workloads.